Strengthening teachers' digital competence through school climate, KSRG program, motivation, and transformational leadership - Aini Septia Rahmalita; Nellitawati Nellitawati; Ahmad Sabandi; Tia Ayu Ningrum (Journal of Educational and Learning Studies, 2026)
This study examines the effects of the Google Reference School Candidate (KSRG) Program, teacher motivation, and transformational leadership on teachers' digital competence through school climate in State Senior High Schools across West Sumatra Province. A quantitative causal research design was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The study involved 481 teachers selected through purposive sampling from State Senior High Schools across West Sumatra. Data were collected using a five-point Likert-scale questionnaire measuring teachers' digital competence, the KSRG Program, teacher motivation, transformational leadership, and school climate. Data were analyzed using SmartPLS to evaluate the measurement model and structural model. The findings indicate that the KSRG Program (β = 0.246, p < 0.001) and teacher motivation (β = 0.843, p < 0.001) have positive and significant effects on teachers' digital competence, whereas transformational leadership has no significant direct effect (β = –0.083, p = 0.061). The KSRG Program, teacher motivation, and transformational leadership significantly influence school climate, while school climate has a significant negative effect on teachers' digital competence (β = –0.145, p = 0.016). Furthermore, school climate significantly mediates the relationships between the KSRG Program, teacher motivation, transformational leadership, and teachers' digital competence. The study concludes that teacher motivation is the strongest determinant of teachers' digital competence, whereas transformational leadership plays the most prominent role in shaping school climate. These findings highlight the importance of integrating motivational, organizational, and digital transformation initiatives through the KSRG Program to strengthen teachers' digital competence.